Acceptability of digital anal cancer screening examinations in HIV‐positive homosexual men. Issue 8 (16th April 2013) - Read, TRH; Vodstrcil, L; Grulich, AE; Farmer, C; Bradshaw, CS; Chen, MY; Tabrizi, S; Hocking, JS; Anderson, J; Fairley, CK
Abstract : Objectives: Anal cancer is more common in HIV‐positive homosexual men than in HIV‐negative homosexual men and the general population. Earlier diagnosis leads to improved prognosis. We aimed to determine if regular anal inspection and digital examination of asymptomatic homosexual men attending for routine HIV care were acceptable and to record the rate of referral for diagnosis of potentially malignant anal lesions. Methods: We offered anal examinations to consecutive homosexual men with HIV infection aged ≥ 35 years during their routine HIV clinic visits, aiming to complete three examinations over a 12‐month period. Acceptability questionnaires were completed at baseline and after each examination and doctors recorded examination findings and all resulting interventions. Hospital referral outcomes were collected and interventions were costed using the Australian Medical Benefits Schedule. Results: Of 142 men who were offered enrolment in the study, 102 [72%; 95% confidence interval (CI) 64–79%] participated. Following the initial anal examinations, four men were referred to surgeons. Cancer was excluded in three men (3%; 95% CI 1–8%) and one was diagnosed with anal squamous cell carcinoma (SCC). Three men had anoscopy performed at the time and two were referred for colonoscopy. Ninety‐eight per cent (95% CI 93–100%) of respondents said that they would probably have the examination next time. The intervention was estimated to cost approximately Australian 16 per examination. Conclusions: Regular anal digital examinations are an acceptable and inexpensive addition to the routine care of homosexual men with HIV infection.